2015
DOI: 10.1136/bjophthalmol-2014-305938
|View full text |Cite
|
Sign up to set email alerts
|

Extending the diabetic retinopathy screening interval beyond 1 year: systematic review

Abstract: To determine whether the recommended screening interval for diabetic retinopathy (DR) in the UK can safely be extended beyond 1 year. Systematic review of clinical and cost-effectiveness studies. Nine databases were searched with no date restrictions. Randomised controlled trials (RCTs), cohort studies, prognostic or economic modelling studies which described the incidence and progression of DR in populations with type 1 diabetes mellitus or type 2 diabetes mellitus of either sex and of any age reporting incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 44 publications
(143 reference statements)
1
63
0
1
Order By: Relevance
“…IS was one of a team of researchers who were involved in a research report produced by the University of Warwick on behalf of the Four Nations Diabetic Retinopathy Study Group entitled 'Rapid literature review: would changing diabetic eye screening intervals from the current annual recommendation lead to changed clinical outcomes?' 54 7. There has been much debate over the years on the influence of one or both eyes on quality-of-life scores and, believing that work in this area would be useful for this HTA project, we undertook a retrospective analysis of data collected in 289 people with diabetic macular oedema at baseline in a randomised clinical trial with diabetic macular oedema, and we recommended that a weighted visual acuity measure from both eyes is considered in future diabetic macular oedema trials.…”
Section: Proposed Time Period For Retention Of Relevant Documentationmentioning
confidence: 99%
“…IS was one of a team of researchers who were involved in a research report produced by the University of Warwick on behalf of the Four Nations Diabetic Retinopathy Study Group entitled 'Rapid literature review: would changing diabetic eye screening intervals from the current annual recommendation lead to changed clinical outcomes?' 54 7. There has been much debate over the years on the influence of one or both eyes on quality-of-life scores and, believing that work in this area would be useful for this HTA project, we undertook a retrospective analysis of data collected in 289 people with diabetic macular oedema at baseline in a randomised clinical trial with diabetic macular oedema, and we recommended that a weighted visual acuity measure from both eyes is considered in future diabetic macular oedema trials.…”
Section: Proposed Time Period For Retention Of Relevant Documentationmentioning
confidence: 99%
“…However, it has been suggested that biomarkers related to these major retinopathy risk factors can be used to guide retinopathy screening intervals so as to increase the costefficiency of this resource. Recent reviews support the extension of retinal screening intervals from the generally recommended annual review to every two years for people with well-controlled type 2 diabetes and no diabetic retinopathy [34,35]. Also, personalized screening intervals have been suggested.…”
Section: Why Use Biomarkers?mentioning
confidence: 99%
“…A systematic review in 2014 looked at the evidence for extending the screening interval beyond 1 year in the UK and did not find robust evidence to support this due to the lack of randomized trials of such an approach. 3 What it did not seem to address is what annual incidence rate justifies screening annually and based on that if any group could have less frequent screening or no screening at all. This is a cost-benefit argument where decisions need to be made on what level of risk of missing sight-threatening retinopathy is acceptable.…”
mentioning
confidence: 99%
“…Siaudvytyte et al 1 further noted that a higher translaminar pressure difference (TPD), that is, the difference of intraocular pressure (IOP) minus ICP, may lead to abnormal function and ON damage due to deformation of the lamina cribrosa, changes in axonal transport, altered blood flow, or a combination of them all. In view of many arguments against the hypothesis that the translaminar imbalance between the IOP and ICP caused by low ICP could have a role in the pathogenesis of glaucoma through a higher TPD acting across the optic nerve head, 3 we present an alternative viewpoint according to which the imbalance between IOP and ICP may reflect the imbalance between production and clearance of neurotoxins in the anterior part of the ON. Indeed, previous findings at least suggest that high IOP may generate inflammatory proteins and neurotoxins, such as amyloid-β (Aβ) that is a hallmark protein in Alzheimer's disease, that could then be cleared via the CSF.…”
mentioning
confidence: 99%
See 1 more Smart Citation